A new genus of Rhinebothriidea from species of Psammobatis (Rajiformes: Arhynchobatidae) off Argentina - Franzese, Sebastian; Ivanov, Veronica A. (Zootaxa, 2020)
Two species of a new genus of Rhinebothriidea have been collected from species of Psammobatis Günther along the coast of Argentina. Semiorbiseptum gen. nov. is considered a rhinebothriidean for the presence of facially loculated bothridia borne on stalks and cirrus covered with spinitriches. The genus is unique in the arrangement of loculi and septa on the distal bothridial surface, including semicircular septa in the middle region. Despite the anterior-posterior orientation of bothridia, Semiorbiseptum gen. nov. fits well in the description of the family Rhinebothriidae by lacking a myzorhynchus at the adult stage and postvaginal testes, and by having vitelline follicles that are not interrupted at the level of the ovary. The two new species differ from each other in the number of facial bothridial loculi and in the microthrix pattern on the proximal bothridial surface. Unlike the majority of rhinebothrideans in the marine environment, which show high specificity for their definitive host, Semiorbiseptum mariae sp. nov. was found in two species of Psammobatis, the smallthorn sand skate Psammobatis rudis Günther and shortfin sand skate Psammobatis normani McEachran. These species have a sympatric distribution, similar to the hosts of most rhinebothrideans that parasitize more than one host. On the contrary, Semiorbiseptum alfredoi sp. nov. was found only in P. normani. This study shows that some of the characters previously proposed as possible synapomorphies for the order have interspecific variability or can be equivocally interpreted (e.g. the entrance of the vas deferens into the cirrus sac, bothridial stalk shape).